Complement and coagulation cascade cross-talk in endometriosis and the potential of Janus Kinase inhibitors—a network meta-analysis - Golinska, Monika; Rycerz, Aleksander; Sobczak, Matylda; Chrzanowski, Jedrzej; Stawiski, Konrad; Fendler, Wojciech (Frontiers in Immunology, 2025)
BackgroundMolecular events that drive endometriosis (EM) and cause accompanying immune deregulation remain elusive. Our purpose was to identify key pathways involved in lesion formation across diverse populations and to detect transcriptomic changes in eutopic endometrium that accompany EM.MethodsWe searched Gene Expression Omnibus and ArrayExpress and performed differential gene expression analysis and a network meta-analysis on nine qualifying datasets. Those contained transcriptomic data on 114 ectopic endometrium samples (EL), 138 eutopic endometrium samples from women with endometriosis (EEM), and 79 eutopic endometrium samples from women without endometriosis (EH). Gene ontology and enrichment analysis were performed in DAVID, Metascape, and Cytoscape, and drug repurposing was done in CMap.ResultsEEM compared to EH upregulated CCL21 and downregulated BIRC3, CEL, and LEFTY1 genes (|log2FC| > 0.5, p < 0.05). EL showed increased expression of complement and serpin genes (EL vs. EEM: C7, logFC = 3.38, p < 0.0001; C3, logFC = 2.40, p < 0.0001; SERPINE1, logFC = 1.02, p < 0.05; SERPINE2, logFC = 1.54, p < 0.001) and mast cell markers (EL vs. EEM: CPA3, logFC = 1.54, p < 0.0001; KIT, logFC = 0.74, p < 0.001). Functional enrichment analysis highlighted complement and coagulation, inflammation, angiogenesis, and extracellular matrix remodeling as drivers of endometriosis. Pharmacogenomic analysis indicated Janus kinase (JAK), cyclin-dependent kinase (CDK), and topoisomerase inhibitors as therapy targets.ConclusionOur results suggest an interplay between complement and coagulation, mast cells, extracellular matrix remodeling, and the JAK/STAT3 pathway in endometriosis. We underscore the significance of complement C3 and propose JAK inhibitors as therapy candidates. Detected expression differences between EEM and EH are important for the development of diagnosis via endometrial biopsy.